2019
DOI: 10.1002/wfp2.12006
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the impact of organic certification on product and sustainable attributes on the importance of organic food certification in Thailand: Mediating role of perceived benefits of organic food

Abstract: Time has come to cope with severe food shortage as well as quality which is resulting in the stunted growth of children and many other diseases. The answer to all these problems lies in organic food which is becoming increasingly common in developed countries as many brands are moving toward organic certification of their products as well as sustainable attributes. This study has aimed to analyze the importance of the role of organic certification of products as well as sustainable attributes in Thailand. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, there are few studies paying attention to the impact of health beliefs on the willingness to purchase organic food from the perspective of health belief theory. Only a small number of scholars have proposed two important factors influencing consumers' selection of organic food, including health benefits and environmental benefits [ 27 ], but health benefits are only regarded as part of perceived benefits. For example, in accordance with the analysis by using attribution theory, Yao Wen found that consumers' perception of the health attributes and environmental protection effects of green agricultural products can significantly influence their willingness to buy green agricultural products [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies paying attention to the impact of health beliefs on the willingness to purchase organic food from the perspective of health belief theory. Only a small number of scholars have proposed two important factors influencing consumers' selection of organic food, including health benefits and environmental benefits [ 27 ], but health benefits are only regarded as part of perceived benefits. For example, in accordance with the analysis by using attribution theory, Yao Wen found that consumers' perception of the health attributes and environmental protection effects of green agricultural products can significantly influence their willingness to buy green agricultural products [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to utilize the bark and leaves of kluwih as an electric mosquito repellent that is environmentally friendly and safe for humans (Mitprasat et al, 2020). In this study kluwih leaves were chosen because the waste from the liquid was found more in the bark and leaves of Figure 2.…”
Section: Introductionmentioning
confidence: 99%